2006
DOI: 10.1111/j.1468-2982.2006.01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Medication Overuse Headache after Abrupt in-Patient withdrawal

Abstract: One hundred and one patients suffering from chronic daily headache (CDH) and medication overuse were treated, in an in-patient setting, with abrupt discontinuation of the medication overused, intravenous hydrating, and intravenous administration of benzodiazepines and ademetionine. The mean time to CDH resolution was 8.8 days. The in-patient withdrawal protocol used was effective, safe and well tolerated. There was a trend for a shorter time to CDH resolution in patients who overused triptans ( P = 0.062). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 30 publications
(55 reference statements)
0
32
1
1
Order By: Relevance
“…In our analysis, no difference was found between triptans and ergot derivatives concerning risk of drug dependence, although some authors previously observed that with ergotamine overuse, there was lower incidence [5], a more rapid occurrence (1.7 vs 2.7 years) [13,36], a lower monthly intake frequency [36], and a shorter time to recovery upon treatment cessation (5 vs. 10 days) [37] than with triptan overuse. This discrepancy in results may be accounted for by the longer observation period of the current study.…”
Section: Discussioncontrasting
confidence: 42%
“…In our analysis, no difference was found between triptans and ergot derivatives concerning risk of drug dependence, although some authors previously observed that with ergotamine overuse, there was lower incidence [5], a more rapid occurrence (1.7 vs 2.7 years) [13,36], a lower monthly intake frequency [36], and a shorter time to recovery upon treatment cessation (5 vs. 10 days) [37] than with triptan overuse. This discrepancy in results may be accounted for by the longer observation period of the current study.…”
Section: Discussioncontrasting
confidence: 42%
“…While withdrawal from tripans is usually uncomplicated and generally does not require supplemental medication [68,69], withdrawal from other medication may require fluid replacement, antiemetics, mono-analgesics (naproxen 500 mg two-to three-times daily), β-blockers or even clonidine for the acute phase. A recently conducted open-label study was able to show that cortisone (oral prednisone 100 mg daily for 3 days then tapering) could considerably reduce withdrawal headache [70].…”
Section: Clinical Managementmentioning
confidence: 99%
“…Compared to barbituates and opioids, patients who overuse triptans have a quicker recovery after withdrawal and are less likely to relapse. 36 Patients who use triptans are also less likely to develop chronic migraine than patients who use opioids or barbiturate-containing medications. 37 Patients with migraine appear to be at risk for worsening of pain with increasing medication use, even compared with patients with other chronic pain disorders.…”
Section: 34mentioning
confidence: 99%